Construction of the Big Walnut Augmentation/Rickenbacker Interceptor Tunnel (BWARI, Part 1) —Columbus, Ohio - Jeremy P. Theys; Mina M. Shinouda; Gary W. Gilbert; Glen D. Frank (Society for Mining, Metallurgy & Exploration, 2007)
PURPOSE OF THE PROJECT The Big Walnut Augmentation Rickenbacker Interceptor project began in 1995with the preparation of the Scope of Services for the design of the Rickenbacker Interceptor, with service to and around the Rickenbacker Air Force base. The air base was soon to be placed under civilian control through a Port Authority, with an expected influx of businesses and services, requiring increased sanitary service capability. Due to political differences regarding annexation and other issues, the project was placed on hold. In mid 1996 the Scope of Services was rewritten with more emphasis on a tunneling option, but still only addressing the air base and surrounding tributary are a sanitary service requirements. The consultant selection process began in late 1996 with the Request for Statements of Qualifications issued in December. Three firms were selected to furnish proposals based on the revised Scope of Services that now included requirements for hydraulic modeling of the service areas and the Big Walnut Outfall (BWO) and an expanded soil investigation requirement. All three firms were requested to make presentations to the selection committee, with the committee selecting URS Greiner for further consideration and negotiation. A contract was entered into in August of 1997with URS Greiner. The major sub-consultants were Lachel and Associates, Inc., H.R.Gray and Associates and Solar Testing Laboratories, Inc. The project began with geological investigations, preliminary soil borings, well investigations, tributary area evaluations, hydraulic modeling of the BWO system and research into other projects planned for the Rickenbacker airport and surrounding area. The hydraulic modeling of the BWO and the proposed Rickenbacker Interceptor confirmed that the BWO suffered wet weather surcharging and would require augmentation to properly convey the future flows to the Southerly Wastewater Treatment Plant(SWWTP). The project scope expanded to include evaluation of both the Rickenbacker Interceptor and the Big Walnut Augmentation projects. Both projects previously identified in the Capital Improvements Program. The work on the expanded scope for the Big Walnut Augmentation and the Rickenbacker Interceptor began with the evaluation of a parallel 2.75 meter (108") diameter augmentation sewer from SWWTP to S.R. 317and Parsons Avenue, then continuing east along S.R. 317 as the Rickenbacker Interceptor. The parallel 2.75 meter (108") sewer had been planned for in the design of